The Role of Warming Up Activities in Adolescent Students' Involvement during the English Class El papel de actividades de motivación inicial en la participación de estudiantes adolescentes en la clase de inglés - Rosalba Velandia (Universidad Nacional de Colombia, 2008)
In this article we want to share the experience we had when we applied warming up activities to seven graders at Porfirio Barba Jacob, a public school in Bogotá, during 2004. Our main objective was to get students' attention at the beginning of the class by means of enjoyable and short activities as well as to observe how possible it was to engage them in the steps that followed. We sought to explore students' involvement in the English class while we tried to motivate them through appropriate warm ups. We used journals, students' surveys and field notes to collect data. The analysis of information collected showed us that the use of warm up activities increases students' attention and helps us link the processes of the class. En este artículo compartimos la experiencia que tuvimos al aplicar actividades de motivación inicial con alumnos de grado séptimo del colegio Porfirio Barba Jacob, una institución pública en Bogotá, durante el año 2004. Nuestro objetivo principal fue captar la atención de nuestros estudiantes mediante actividades cortas y divertidas al comienzo de la clase, que los comprometieran con las siguientes etapas de la misma. Exploramos la participación de los estudiantes en la clase de inglés motivándolos a través de actividades de iniciación adecuadas. Para la recolección de datos empleamos diarios, entrevistas a alumnos y el diario de campo. El análisis de la información recolectada mostró que el uso de actividades de iniciación incrementa la atención de los estudiantes y ayudan a conectar los procesos de la clase.